A positive solution of singular impulsive differential equations with nonlinear boundary conditions - Weibing Wang; Jianhua Shen (Нелінійні коливання, 2014)
By using priori estimates and the theory of topological degree, we study the existence of positive solution to a class of second order singular impulsive differential equations with nonlinear boundary conditions. Our result admits that the nonlinear term of differential equation can be singular in its second and third variable